2009
DOI: 10.1161/circheartfailure.109.851246
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Heart Failure and the Value of β-Blockers Are Altered by the Use of Antidepressants and Depend on the Type of Antidepressants Used

Abstract: Background-Depression worsens the prognosis in patients with cardiac disease, and treatment with antidepressants may improve survival. Guidelines recommend use of selective serotonin reuptake inhibitors (SSRIs), but knowledge of the prognostic effect of different classes of antidepressants is sparse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 43 publications
(52 reference statements)
1
36
0
6
Order By: Relevance
“…The consequences of coexistence of heart failure and depression include a poorer quality of life, stronger perception of complaints, nonadherence, higher rates of mortality and clinical events, rehospitalization and general health care burden [34]. Despite an obvious need to diagnose depression, to date, evidence of benefits of depression treatment in HF patients is lacking, and sparse existing studies provide conflicting results [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of coexistence of heart failure and depression include a poorer quality of life, stronger perception of complaints, nonadherence, higher rates of mortality and clinical events, rehospitalization and general health care burden [34]. Despite an obvious need to diagnose depression, to date, evidence of benefits of depression treatment in HF patients is lacking, and sparse existing studies provide conflicting results [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study identified the coadministration of SSRIs and beta-blockers in patients with heart failure to have a higher risk of death than TCAs (HR 1. [179]. Remission from depression may improve survival in patients with CHF [180]; however, depression could still persist despite antidepressant use, and this does not improve survival.…”
Section: Depressionmentioning
confidence: 99%
“…An important component of managing depression and anxiety is the management of other symptoms, such as dyspnea and pain. While anti-depressants are commonly employed in the general patient population with depression, a recent observational study showed that the use of selective serotonin reuptake inhibitors (SSRIs) or tricyclic antidepressants (TCAs) in the HF patient population was associated with an increased risk of death (Fosbøl et al 2009). In terms of SSRIs, this study showed that risk was further potentiated when they were co-administered with beta-blockers.…”
Section: Depression and Anxietymentioning
confidence: 99%